The (Not So) Evil Within? Agency in Video Game Choice and the Impact of Violent Content. (June 2017) - Ferguson, Christopher J.; Colon-Motas, Kay; Esser, Carolin; Lanie, Connor; Purvis, Skylar; Williams, Mark
Background . The degree to whichviolent video games do, or do not contribute toaggressive behavior andhostility remains controversial in the scientific community, with scholars not yet having come to a consensus about effects. Recent studies have examined whether other issues such as frustration or competition might explain some video game influences that were previously thought to be due to violent content. Aim . The current study examines whether playeragency in determining choice of game played influences aggressive outcomes. Methods . Young adult players were randomized either to play a violent game, a non-violent game, or to be given the choice between several violent and non-violent games. Players were examined for subsequent aggressive behavior using the ice water task as well as for stress levels and hostility. Results . Game condition did not influence hostility, stress, or aggressive behavior, whether with randomized or chosen games. Conclusion . The present study provided no evidence that violent video games contribute to aggressive behavior. Lack of influence for agency in game choice can be understood given the lack of any aggression effect for violent game exposure.